The effectiveness of the Algerian women’s protection and And supporting their participation in various aspects of life - bin Ali, Azizo Abdul Rahman (Journal of Humanities & Social Sciences, 2018)
This study is for identifying the Women’s protection system in Algeria; and the status occupied by Algerian women today after the development in the world as a whole; The study adopted the analytical approach; it has studied the statistics and legal texts governing the work of women in Algeria. The study dealt with four aspects: the legal aspect, the popular and individual culture towards women in Algerian society the diagnosis of the reality of working women and the difficulties they face The study found that the situation of Algerian women in general has developed, but is still not satisfactory, and it made several recommendations related to all fields (socio-political, economic, cultural)